Perfect state transfer in two dimensions and the bivariate dual-Hahn polynomials. (19th April 2022) - Miki, Hiroshi; Tsujimoto, Satoshi; Vinet, Luc
Abstract: A new solvable 2D spin lattice model defined on a regular grid of triangular shape is proposed. The hopping amplitudes between sites are related to recurrence coefficients of certain bivariate dual-Hahn polynomials. For a specific choice of the parameters, perfect state transfer and fractional revival are shown to take place.